Contrasting effects of NADPH oxidases on the fungal hyphae growth and immune responses in Pleurotus ostreatus - Li, Huiping; Zhu, Jiachun; Li, Zihao; Xu, Ping; Ma, Lin; Zou, Yajie; Qu, Shaoxuan; Wu, Xiaoqin (Frontiers in Microbiology, 2024)
Pleurotus ostreatus is one of the most consumed mushroom species, as it serves as a high-quality food, favors a rich secondary metabolism, and has remarkable adaptability to the environment and predators. In this study, we investigated the function of two key reactive oxygen species producing enzyme NADPH oxidase (PoNoxA and PoNoxB) in P. ostreatus hyphae growth, metabolite production, signaling pathway activation, and immune responses to different stresses. Characterization of the Nox mutants showed that PoNoxB played an important role in the hyphal formation of the multicellular structure, while PoNoxA regulated apical dominance. The ability of P. ostreatus to tolerate a series of abiotic stress conditions (e.g., osmotic, oxidative, membrane and cell-wall stresses) and mechanical damage repair was enhanced with PoNoxA over-expression. PoNoxB had a greater responsibility in regulating the polysaccharide composition of the cell wall and methyl jasmonate and gibberellin GA1 biosynthesis, andimproved mushroom resistance against Tyrophagus putrescentiae. Moreover, mutants were involved in the jasmonate and GA signaling pathway, and toxic protein defense metabolite production. Our findings shed light on how the oyster mushroom senses stress signals and responds to adverse environments by the complex regulators of Noxs. Davalli et al., 2016). ROS, particularly hydrogen peroxide (H2O2), were initially considered to be cytotoxic and continuously produced through diverse cellular responses to stimuli (Mittler, 2017). More recently, ROS have been recognized as key signaling molecules that regulate gene expression,